Ternary single crystal positive electrode material, preparation method thereof and battery

By adopting the preparation method of ternary single crystal positive electrode material, the problems of unstable structure and poor circulation performance of the existing positive electrode material are solved by two sintering and controlling the mole ratio of lithium salt, and a battery with high volume energy density and good circulation performance is achieved.

CN119660828APending Publication Date: 2025-03-21YIBIN LIBODE NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411804171.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

While the existing lithium-ion battery positive electrode materials increase the volume specific energy density, there are problems of structural instability and poor circulation performance.

Method used

By using the preparation method of ternary single crystal positive electrode material, the precursor of ternary positive electrode material is mixed with the lithium salt and sintered twice, and the molar ratio of the lithium salt is controlled to improve the spherical shape and tap density of the material.

Benefits of technology

It effectively improves the spherical shape and tap density of the ternary single crystal positive electrode material, thereby improving the volume energy density of the material, and improving the specific capacity and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660828A_ABST
    Figure CN119660828A_ABST
Patent Text Reader

Abstract

The invention discloses a ternary single crystal positive electrode material, a preparation method thereof and a battery, and belongs to the technical field of battery materials. The preparation method of the ternary single-crystal positive electrode material comprises the following steps: mixing a ternary positive electrode material precursor with a first lithium salt, and carrying out first sintering to obtain a first sintered material; mixing the first sintering material with a second lithium salt, and carrying out second sintering; the ratio of the molar weight of Li in the first lithium salt to the total molar weight of metals in the ternary positive electrode material precursor is 0.6: 1 to 0.85: 1; the ratio of the total molar weight of Li in the first lithium salt and Li in the second lithium salt to the total molar weight of metal in the ternary positive electrode material precursor is 1.05: 1. The method is simple to operate, the sphericity and the tap density of the ternary single crystal positive electrode material can be effectively improved by adopting two times of lithium supplementation and controlling the lithium ratio of each time of lithium supplementation, so that the volume energy density of the material is further improved, and the specific capacity and the cycle performance of a battery prepared from the positive electrode material are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a ternary single crystal positive electrode material and a preparation method thereof and a battery. Background Art

[0002] The energy density of lithium-ion batteries is one of their key performance indicators, which is related to the battery's endurance. The volumetric specific energy of the positive electrode material is an important factor affecting the energy density of lithium-ion batteries. Therefore, how to improve the volumetric specific energy of the positive electrode material has become a research hotspot in the field of lithium-ion batteries.

[0003] In the prior art, high-nickel, low-cobalt or cobalt-free positive electrode materials are generally used to increase the nickel content to improve the specific capacity of the material. Although high-nickel, low-cobalt or cobalt-free positive electrode materials can increase the nickel content and thus improve the specific capacity of the material, they also bring about problems such as unstable material structure and poor cycle performance.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a ternary single crystal positive electrode material and a preparation method and a battery, so as to solve or improve the above technical problems.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps: mixing a ternary positive electrode material precursor with a first lithium salt and then performing a first sintering to obtain a first sintered material; mixing the first sintered material with a second lithium salt and then performing a second sintering to obtain a ternary single crystal positive electrode material;

[0008] The ratio of the molar amount of Li in the first lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is 0.6:1 to 0.85:1;

[0009] The ratio of the total molar amount of Li in the first lithium salt and the total molar amount of Li in the second lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is 1.05:1.

[0010] In an alternative embodiment, the first lithium salt includes at least one of lithium carbonate and lithium hydroxide.

[0011] In an optional embodiment, the temperature of the first sintering is 600° C. to 900° C., the time of the first sintering is 6 h to 10 h, and the first sintering is performed in an oxygen atmosphere.

[0012] In an alternative embodiment, the second lithium salt includes at least one of lithium carbonate and lithium hydroxide.

[0013] In an optional embodiment, the temperature of the second sintering is 700° C. to 1000° C., the time of the second sintering is 8 h to 15 h, and the second sintering is performed in an oxygen atmosphere.

[0014] In an optional embodiment, the first sintered material is crushed to 2.5 μm to 5.0 μm and then mixed with the second lithium salt.

[0015] In an optional embodiment, the chemical formula of the ternary cathode material precursor is Ni x Co y Mn z (OH)2, wherein the value of x is 0.3-0.95, the value of y is 0.05-0.3, and z=1-xy.

[0016] In a second aspect, the present invention provides a ternary single crystal positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.

[0017] In an optional embodiment, the tap density of the ternary single crystal positive electrode material is not less than 2.6 g / cm 3 .

[0018] In a third aspect, the present invention provides a battery, wherein the raw materials for preparing the battery include the ternary single crystal positive electrode material of the aforementioned embodiment.

[0019] The beneficial effects of the present invention include:

[0020] The method for preparing the ternary single crystal positive electrode material provided by the present invention is simple to operate. By adopting two lithium replenishments and controlling the lithium ratio of each lithium replenishment, the sphericity and tap density of the ternary single crystal positive electrode material can be effectively improved, thereby increasing the volume energy density of the material, which is beneficial to improving the specific capacity and cycle performance of the battery prepared from the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 This is a SEM image of the ternary single crystal positive electrode material prepared in Example 1;

[0023] Figure 2 This is a SEM image of the ternary single crystal positive electrode material prepared in Example 2;

[0024] Figure 3This is a SEM image of the ternary single crystal positive electrode material prepared in Example 3;

[0025] Figure 4 This is the SEM image of the ternary single crystal positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0027] The ternary single crystal positive electrode material and its preparation method and battery provided by the present invention are described in detail below.

[0028] The present invention provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps: mixing a ternary positive electrode material precursor with a first lithium salt and then performing a first sintering to obtain a first sintered material; mixing the first sintered material with a second lithium salt and then performing a second sintering to obtain a ternary single crystal positive electrode material.

[0029] Among them, the ratio of the molar amount of Li in the first lithium salt to the total molar amount of metal in the ternary positive electrode material precursor is 0.6:1 to 0.85:1, such as 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1 or 0.85:1, etc., and can also be other values ​​within the range of 0.6:1 to 0.85:1.

[0030] The ratio of the molar amount of Li in the first lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is controlled within a range of 0.6:1 to 0.85:1, so that the morphology of the first sintered material particles can be rounded. If the ratio of the molar amount of Li in the first lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is lower than 0.6:1, it is not conducive to the formation of a layered structure; if the ratio of the molar amount of Li in the first lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is higher than 0.85:1, it is not conducive to the formation of a high sphericity positive electrode material.

[0031] The ratio of the total molar amount of Li in the first lithium salt and the total molar amount of Li in the second lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is 1.05: 1. Under this ratio, it is beneficial to further obtain a ternary single crystal positive electrode material with good sphericity and high tap density from the first sintered material with a rounded morphology.

[0032] If the ratio of the total molar amount of Li in the first lithium salt and the total molar amount of Li in the second lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is lower than 1.05:1 (such as 0.95:1), it is easy to cause the positive electrode material to have a low capacity and contain metal oxide impurities; if the ratio of the total molar amount of Li in the first lithium salt and the total molar amount of Li in the second lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is higher than 1.05:1 (such as 1.1:1), it is easy to cause the residual alkali in the material to be high and the capacity to be low.

[0033] As mentioned above, the method for preparing the ternary single crystal positive electrode material provided by the present invention is simple to operate. By adopting two lithium replenishments and controlling the lithium ratio of each lithium replenishment (that is, the molar ratio of Li in the lithium salt to the mixed metal in the ternary positive electrode material precursor), the sphericity and tap density of the ternary single crystal positive electrode material can be effectively improved, thereby increasing the volume energy density of the material, which is beneficial to improving the specific capacity and cycle performance of the battery prepared from the positive electrode material.

[0034] In some optional embodiments, the first lithium salt may include at least one of lithium carbonate and lithium hydroxide, for example.

[0035] The temperature of the first sintering is 600°C to 900°C, such as 600, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C or 900°C, and may also be other values ​​within the range of 600°C to 900°C.

[0036] The first sintering time may be 6 h to 10 h, such as 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h or 10 h, etc., or other values ​​within the range of 6 h to 10 h.

[0037] The first sintering can be performed in an oxygen atmosphere.

[0038] Similarly, the second lithium salt may also include at least one of lithium carbonate and lithium hydroxide.

[0039] The temperature of the second sintering can be 700℃~1000℃, such as 700℃, 750℃, 800℃, 850℃, 900℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃, 990℃ or 1000℃, etc., or it can be other values ​​within the range of 700℃~1000℃.

[0040] The second sintering time can be 8h to 15h, such as 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h or 15h, or other values ​​within the range of 8h to 15h.

[0041] The second sintering can be performed in an oxygen atmosphere.

[0042] In some embodiments, the first sintered material is crushed to 2.5 μm to 5.0 μm before being mixed with the second lithium salt.

[0043] By crushing to the above-mentioned particle size range, it is beneficial to improve the mixing effect of the first sintering material and the second lithium salt.

[0044] In some optional embodiments, the chemical formula of the ternary cathode material precursor is Ni x Co y Mn z (OH)2, wherein the value of x is 0.3-0.95, the value of y is 0.05-0.3, and z=1-xy.

[0045] The precursor of the ternary positive electrode material can be directly purchased or prepared by oneself by referring to relevant existing technologies.

[0046] Correspondingly, the present invention also provides a ternary single crystal positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.

[0047] The tap density of the ternary single crystal positive electrode material is not less than 2.6 g / cm 3 .

[0048] In addition, the present invention also provides a battery, the raw materials for preparing the battery include the above-mentioned ternary single crystal positive electrode material.

[0049] The battery has high specific capacity and good cycle performance.

[0050] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0051] Example 1

[0052] This embodiment provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps:

[0053] S1: 3 kg of the ternary cathode material precursor is mixed with the first lithium salt and then sintered for the first time to obtain a first sintered material.

[0054] Among them, the precursor of the ternary cathode material is Ni 0.6 Co 0.1 Mn 0.3 (OH)2, the first lithium salt is lithium carbonate, the molar amount of Li in lithium carbonate is equal to Ni 0.6 Co 0.1 Mn 0.3 The total molar ratio of Ni, Co and Mn in (OH)2 is 0.8.

[0055] The first sintering temperature is 900°C, the first sintering time is 8 hours, and the first sintering is carried out in an oxygen atmosphere.

[0056] S2: The first sintered material is crushed to a particle size of 3.5 μm to obtain a crushed material.

[0057] S3: The crushed material is mixed with a second lithium salt and then sintered for a second time to obtain a ternary single crystal positive electrode material.

[0058] Among them, the second lithium salt is lithium carbonate, and the ratio of the total molar amount of Li in the lithium carbonate added in S1 and the lithium carbonate added in S3 to the total molar amount of Ni, Co and Mn in the ternary positive electrode material precursor is 1.05:1.

[0059] The second sintering temperature is 980° C., the second sintering time is 10 h, and the second sintering is performed in an oxygen atmosphere.

[0060] Example 2

[0061] This embodiment provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps:

[0062] S1: 3 kg of the ternary cathode material precursor is mixed with the first lithium salt and then sintered for the first time to obtain a first sintered material.

[0063] Among them, the precursor of the ternary cathode material is Ni 0.6 Co 0.1 Mn 0.3 (OH)2, the first lithium salt is lithium hydroxide, the molar amount of Li in lithium carbonate is equal to Ni 0.6 Co 0.1 Mn 0.3 The total molar ratio of Ni, Co and Mn in (OH)2 is 0.8.

[0064] The first sintering temperature is 750°C, the first sintering time is 8 hours, and the first sintering is carried out in an oxygen atmosphere.

[0065] S2: The first sintered material is crushed to a particle size of 3.5 μm to obtain a crushed material.

[0066] S3: The crushed material is mixed with a second lithium salt and then sintered for a second time to obtain a ternary single crystal positive electrode material.

[0067] Among them, the second lithium salt is lithium hydroxide, and the ratio of the total molar amount of Li in the lithium hydroxide added in S1 and the lithium hydroxide added in S3 to the total molar amount of Ni, Co and Mn in the ternary positive electrode material precursor is 1.05:1.

[0068] The second sintering temperature is 980°C, the second sintering time is 10 hours, and the second sintering is carried out in an oxygen atmosphere.

[0069] Example 3

[0070] This embodiment provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps:

[0071] S1: 3 kg of the ternary cathode material precursor is mixed with the first lithium salt and then sintered for the first time to obtain a first sintered material.

[0072] Among them, the precursor of the ternary cathode material is Ni 0.6 Co 0.1 Mn 0.3 (OH)2, the first lithium salt is lithium carbonate, the molar amount of Li in lithium carbonate is equal to Ni 0.6 Co 0.1 Mn 0.3 The total molar ratio of Ni, Co and Mn in (OH)2 is 0.8.

[0073] The first sintering temperature is 900°C, the first sintering time is 8 hours, and the first sintering is carried out in an oxygen atmosphere.

[0074] S2: The first sintered material is crushed to a particle size of 4.5 μm to obtain a crushed material.

[0075] S3: The crushed material is mixed with a second lithium salt and then sintered for a second time to obtain a ternary single crystal positive electrode material.

[0076] Among them, the second lithium salt is lithium carbonate, and the ratio of the total molar amount of Li in the lithium carbonate added in S1 and the lithium carbonate added in S3 to the total molar amount of Ni, Co and Mn in the ternary positive electrode material precursor is 1:1.

[0077] The second sintering temperature is 1000° C., the second sintering time is 10 h, and the second sintering is performed in an oxygen atmosphere.

[0078] Example 4

[0079] This embodiment provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps:

[0080] S1: 3 kg of the ternary cathode material precursor is mixed with the first lithium salt and then sintered for the first time to obtain a first sintered material.

[0081] Among them, the precursor of the ternary cathode material is Ni 0.7 Co 0.1 Mn 0.2(OH)2, the first lithium salt is lithium carbonate, and the ratio of the molar amount of Li in the lithium carbonate to the total molar amount of Ni, Co, and Mn in the ternary positive electrode material precursor is 0.6:1.

[0082] The temperature of the first sintering is 600° C., the time of the first sintering is 10 h, and the first sintering is performed in an oxygen atmosphere.

[0083] S2: The first sintered material is crushed to a particle size of 3.5 μm to obtain a crushed material.

[0084] S3: The crushed material is mixed with a second lithium salt and then sintered for a second time to obtain a ternary single crystal positive electrode material.

[0085] Among them, the second lithium salt is lithium carbonate, and the ratio of the total molar amount of Li in the lithium carbonate added in S1 and the lithium carbonate added in S3 to the total molar amount of Ni, Co and Mn in the ternary positive electrode material precursor is 1.05:1.

[0086] The second sintering temperature is 930° C., the second sintering time is 12 h, and the second sintering is performed in an oxygen atmosphere.

[0087] Example 5

[0088] This embodiment provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps:

[0089] S1: 3 kg of the ternary cathode material precursor is mixed with the first lithium salt and then sintered for the first time to obtain a first sintered material.

[0090] Among them, the precursor of the ternary cathode material is Ni 0.8 Co 0.1 Mn 0.1 (OH)2, the first lithium salt is lithium hydroxide, and the ratio of the molar amount of Li in the lithium hydroxide to the total molar amount of Ni, Co, and Mn in the ternary positive electrode material precursor is 0.85:1.

[0091] The first sintering temperature is 700° C., the first sintering time is 6 h, and the first sintering is performed in an oxygen atmosphere.

[0092] S2: The first sintered material is crushed to a particle size of 3.5 μm to obtain a crushed material.

[0093] S3: The crushed material is mixed with a second lithium salt and then sintered for a second time to obtain a ternary single crystal positive electrode material.

[0094] Among them, the second lithium salt is lithium hydroxide, and the ratio of the total molar amount of Li in the lithium hydroxide added in S1 and the lithium hydroxide added in S3 to the total molar amount of Ni, Co and Mn in the ternary positive electrode material precursor is 1.05:1.

[0095] The second sintering temperature is 830° C., the second sintering time is 8 h, and the second sintering is performed in an oxygen atmosphere.

[0096] Comparative Example 1

[0097] The present embodiment provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps: 3 kg of a ternary positive electrode material precursor is uniformly mixed with a lithium salt at one time and then sintered to obtain a ternary single crystal positive electrode material.

[0098] Among them, the precursor of the ternary cathode material is Ni 0.6 Co 0.1 Mn 0.3 (OH)2, the lithium salt is lithium carbonate, the molar amount of Li in lithium carbonate is equal to Ni 0.6 Co 0.1 Mn 0.3 The total molar ratio of Ni, Co and Mn in (OH)2 is 0.9: 1. The sintering temperature is 980°C, the sintering time is 10 hours, and the sintering is carried out in an oxygen atmosphere.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 1 is that in S1, the ratio of the molar amount of Li in the first lithium salt to the total molar amount of metals in the ternary positive electrode material precursor is 0.55:1.

[0101] Comparative Example 3

[0102] The difference between this comparative example and Example 1 is that in S1, the ratio of the molar amount of Li in the first lithium salt to the total molar amount of metals in the ternary positive electrode material precursor is 0.9:1.

[0103] Comparative Example 4

[0104] The difference between this comparative example and Example 1 is that in S3, the ratio of the total molar amount of Li in the first lithium salt and the Li in the second lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is 0.95:1.

[0105] Comparative Example 5

[0106] The difference between this comparative example and Example 1 is that in S3, the ratio of the total molar amount of Li in the first lithium salt and the total molar amount of Li in the second lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is 1.1:1.

[0107] Comparative Example 6

[0108] The difference between this comparative example and Example 1 is that the first sintering material is directly mixed with the second lithium salt without being crushed, and then sintered for the second time.

[0109] That is, step S2 in Example 1 was not performed in this comparative example.

[0110] Test example

[0111] ①, taking the ternary single crystal positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 as examples, the SEM images of the ternary single crystal positive electrode materials are as follows: Figures 1 to 4 shown.

[0112] Depend on Figures 1 to 3 It can be seen that the positive electrode material particles have a high degree of single crystallization, and the particles are elliptical and relatively round. This is because lithium salts themselves promote growth. The first addition of some lithium salts makes the entire positive electrode material lack lithium during the sintering process, which can prevent the particles from growing further and better inherit the shape of the precursor. The role of secondary lithium supplementation sintering is to repair the material so that the lithium content inside the positive electrode material obtained by the secondary sintering lithium supplementation process is consistent with the lithium content of the primary sintering process, and the entire capacity of the positive electrode material is also consistent. Therefore, the resulting positive electrode material not only guarantees the capacity, but also has a higher tap density.

[0113] Figure 4 This is the product morphology corresponding to the single sintering process without lithium supplementation. It can be seen from the figure that the roundness of the obtained positive electrode material particles is poor (such as the circle), which means that during the sintering process, the entire growth direction of the positive electrode particles is irregular and the precursor morphology is not well inherited, resulting in a low tap density of the material.

[0114] ②. The ternary single crystal positive electrode materials obtained in Examples 1 to 5 and Comparative Examples 1 to 6 were respectively prepared into button-type batteries and subjected to electrochemical performance tests.

[0115] The preparation method of button cell is as follows: the prepared cathode material finished product is mixed as active material with binder polyvinylidene fluoride (PVDF) and conductive agent acetylene black in a mass ratio of 90:5:5 and ground evenly, then a certain amount of nitrogen methyl pyrrolidone (NMP) is added as a dispersant to disperse the mixture, and it is ground into a uniform slurry again and coated on aluminum foil. The coated electrode material is dried in a vacuum oven at 110°C, and then the dried electrode material is rolled by a roller machine, and then dried in a vacuum oven at 120°C for 12h. The dried electrode material is punched, weighed, and the battery is assembled in a glove box. The electrolyte used for assembling the battery is an electrolyte composed of DMC+EC solvent containing 1 mol / L LiPF6, and the electrode sheet of the cathode material is used as the working electrode and the lithium sheet is used as the counter electrode. Button cell test conditions: 0.1C discharge specific capacity is tested at 25°C and 2.8V~4.4V charge and discharge voltage range. The cycle performance test was carried out at 25°C, 2.8V to 4.4V voltage range and 1C / 1C rate.

[0116] The test results are shown in Table 1, where the tap density is tested using a BT-301 tap density tester in accordance with the GB / T5162-2006 method.

[0117] Table 1 Test results

[0118]

[0119] It can be seen from Table 1 that the ternary single crystal positive electrode material prepared in the embodiment of the present invention has better sphericity and higher tap density than the ternary single crystal positive electrode material prepared in the comparative example. The battery prepared by the ternary single crystal positive electrode material provided in the above embodiment has a higher discharge gram capacity and capacity retention rate.

[0120] In summary, the preparation method provided by the present invention can effectively improve the sphericity and tap density of the ternary single crystal positive electrode material, thereby increasing the volume energy density of the material, which is beneficial to improving the capacity and cycle performance of the battery prepared from the positive electrode material.

[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a ternary single crystal positive electrode material, characterized in that: The following steps are involved: Mixing the ternary cathode material precursor with the first lithium salt and performing a first sintering to obtain a first sintered material; The first sintered material is mixed with a second lithium salt and then sintered for a second time to obtain a ternary single crystal positive electrode material; The ratio of the molar amount of Li in the first lithium salt to the total molar amount of metal in the ternary positive electrode material precursor is 0.6:1 to 0.85:1; The ratio of the total molar amount of Li in the first lithium salt and the Li in the second lithium salt to the total molar amount of the metal in the ternary positive electrode material precursor is 1.05:

1.

2. The preparation method according to claim 1, characterized in that: The first lithium salt includes at least one of lithium carbonate and lithium hydroxide.

3. The preparation method according to claim 1, characterized in that: The temperature of the first sintering is 600° C. to 900° C., the time of the first sintering is 6 h to 10 h, and the first sintering is performed in an oxygen atmosphere.

4. The preparation method according to claim 1, characterized in that: The second lithium salt includes at least one of lithium carbonate and lithium hydroxide.

5. The preparation method according to claim 1, characterized in that: The temperature of the second sintering is 700° C. to 1000° C., the time of the second sintering is 8 h to 15 h, and the second sintering is performed in an oxygen atmosphere.

6. The preparation method according to claim 1, characterized in that: The first sintered material is crushed into 2.5 μm to 5 μm and then mixed with the second lithium salt.

7. The preparation method according to claim 1, characterized in that: The chemical formula of the ternary cathode material precursor is Ni x Co y Mn z (OH)2, wherein the value of x is 0.3-0.95, the value of y is 0.05-0.3, and z=1-xy.

8. A ternary single crystal positive electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.

9. The ternary single crystal positive electrode material according to claim 8, characterized in that: The tap density of the ternary single crystal positive electrode material is not less than 2.6 g / cm 3 .

10. A battery, characterized in that: The raw materials for preparing the battery include the ternary single crystal positive electrode material as described in claim 8 or 9.

Citation Information

Patent Citations

  • Lithium-rich multi-element positive electrode material, preparation method thereof, positive electrode and lithium ion power battery

    CN111082041A

  • Nickel-rich material and preparation method thereof, positive plate, battery and electric equipment

    CN114275828A

  • Monocrystal ternary positive electrode material, preparation method thereof and lithium ion battery

    CN115676911A

  • Single crystal type ternary positive electrode material and preparation method thereof

    CN117756193A

  • Triple-fired ternary positive electrode material as well as preparation method and application thereof

    CN118811877A